Prosedur Pembayaran Kas Bank Dan Cash Flow Pada PG. Lestari PT. Sinergi Gula Nusantara - Khoirun Nisak Shabira; Nurhadi Nurhadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out what the bank cash payment procedures and cash flow are in PG. Lestari PT. Nusantara Sugar Synergy. The research method used in this journal uses data collection techniques in the form of observation, interviews and documentation. The results of this research show that having bank cash payment procedures and cash flow can make it easier for a company to record financial reports sequentially and in detail. Having procedures makes it easier to make payments accurately, consistently and relevantly. The conclusion of this research is that the existence of bank cash payment procedures and cash flow is very important in a company because you can know the order of payments in the company so that you cannot make payments at will.